Investigação sobre o impacto da reologia da suspensão frente a um hidrociclone cônico-filtrante - Morimoto, Murilo Guimarães (2021)
The hydrocyclone is an equipment used in order to separate a discrete solid phase from another continuous liquid phase, the FEQUI/UFU institution have several studies investigating this device. The institution when combining the hydrocyclone operation with the filtration operation, created the so-called filtering hydrocyclone, which has operational advantages when compared to a conventional hydrocyclone of the same geometry. One of the researches carried out by the institution proposed a conventional geometrically optimized device whose objective was to achieve high efficiencies (HGOT1) when operated with Newtonian and diluted suspensions. Yet, several suspensions used in the chemical industry are non-Newtonian and concentrated suspensions. Hence, this work aims to evaluate the performance of two hydrocyclones, both geometrically inspired by the HGOT1, one being modified and having a cone made of filtering material and the other a conventional one (without the filtering media). Through a design of experiments, it was possible to study the effect of the volumetric concentration of solids fed, the pressure drop experienced by the hydrocyclones and the effect of the rheology of the fed suspension. Also, a three-dimensional, single-phase, transient state simulation involving the filtering hydrocyclone was conducted in order to develop an approach that is capable to describe this equipment. In conclusion, it was observed that the increase of the apparent viscosity and concentration of the suspension harmed the separation performance of hydrocyclones. When comparing the responses generated by conventional and filtering equipment, it was observed that they differ. The average total efficiency of conventional equipment was 4.1% lower than that of the filtering one. While the average Euler number of the filtering equipment was approximately 12% lower than the conventional one. It is believed, that even when operating with non-Newtonian and concentrated suspensions, the presence of the filter was able to change the fluid dynamics of the equipment, which guaranteed the filtering hydrdorcylclone an advantage in separation performance and energy consumption when compared to the conventional one.